Influence of Social Media Shopping on Buying Behaviour of college students. A Case of Rapti Babai Campus - Shrestha, Rojina (Journal of Rapti Babai Campus, 2025)
This research examines how social media influences college students in terms of their social media shopping behaviour, preferences, and decision-making processes. Through a structured questionnaire administered to a sample of 54 college students, data were collected and analyzed with the help of descriptive statistics and Pearson correlation to uncover patterns and correlations between social media usage and online shopping behaviour. The findings highlight significant insights into the role of social media shopping platforms in shaping (consumer attitudes, purchase intentions, and behaviour) in the online shopping domain. Ultimately, this research contributes to the existing literature by providing empirical evidence of the transformative influence of social media shopping on the online behavior of today’s college students. The study also highlights the key indicators that majorly affect the consumer behavior and shopping attitude especially the college students and the transition of shopping pattern from physical shopping to digital shopping. Through the study, one can be aware of the popularity of social media platforms for shopping purposes among college students.